Patterns of inflammatory lesions of the appendix in a Nigerian Tertiary Health Facility (2021)
Background: Appendicitis is most common between the ages of 10 and 20 years, although all ages can be affected. Acute appendicitis is the most common cause of acute surgical abdomen worldwide and its incidence varies with geographical location. The aim of this study was to review all the inflammatory lesions of the surgically removed appendix in University College Hospital, Ibadan, Nigeria and to describe the histopathological patterns of these lesions. Methods: This study was a retrospective review of all appendectomy specimens submitted to the Department of Pathology, University College Hospital, Ibadan, Nigeria from January 2009 to December 2018. Patients’ biodata, clinical parameters, and histological diagnoses were extracted from departmental surgical day books. The data were analyzed using IBM SPSS Statistics (version 23; IBM Corporation, Armonk, New York) and expressed as frequency distribution. Results: A total of 1071 appendectomy specimens were received in our laboratory during the 10-year study period, accounting for 3% of all specimens received. There were 1062 cases of inflammatory lesions, accounting for 99.2% of the cases. There was a male preponderance with male to female ratio of 1.2:1. The age was from 1 to 83 years. The most common histological diagnosis was acute suppurative appendicitis with peritonitis accounting for 47.6% of all the cases. Conclusion: The findings in our study supports the fact that acute suppurative appendicitis is the most common inflammatory disease of the appendix which is consistent with other similar studies that have been done in our environment and in the developed world.